2015
DOI: 10.1093/ehjci/jev153
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological stress cardiovascular magnetic resonance: feasibility and safety in a large multicentre prospective registry

Abstract: Performance of stress CMR is safe in a referral population. Inducible ischaemia was the only factor identified which was associated with serious complications. The incidence of non-severe complications and minor symptoms was greater with dobutamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
1
15
1
1
Order By: Relevance
“…A comprehensive comparison of medications (adenosine, regadenoson, dipyridamole, and dobutamine) available for stress CMR is presented in TABLE 1. [39][40][41][42][43][44][45][46][47][48][49][50][51] Vasodilator stress perfusion cardiac magnetic resonance imaging During perfusion CMR, the first--pass transit of a gadolinium -based CM through the LV myocardium is observed under hyperemia mediated by infusion of a vasodilator. In the healthy myocardium, the coronary microvasculature dilates during exercise and stress ensuring suitable tissue perfusion, whereas for significantly stenosed coronary arteries, the distal microvasculature is almost maximally dilated under rest conditions and hyperemia provoked by vasodilators triggers a coronary steal effect.…”
mentioning
confidence: 99%
“…A comprehensive comparison of medications (adenosine, regadenoson, dipyridamole, and dobutamine) available for stress CMR is presented in TABLE 1. [39][40][41][42][43][44][45][46][47][48][49][50][51] Vasodilator stress perfusion cardiac magnetic resonance imaging During perfusion CMR, the first--pass transit of a gadolinium -based CM through the LV myocardium is observed under hyperemia mediated by infusion of a vasodilator. In the healthy myocardium, the coronary microvasculature dilates during exercise and stress ensuring suitable tissue perfusion, whereas for significantly stenosed coronary arteries, the distal microvasculature is almost maximally dilated under rest conditions and hyperemia provoked by vasodilators triggers a coronary steal effect.…”
mentioning
confidence: 99%
“…The excellent safety profile of stress CMR was demonstrated in a large registry of 11,984 patients using dipyridamole or dobutamine ( 74 ) and in the EuroCMR registry assessing 10,228 patients referred for stress CMR ( 31 ). The incidence of severe complications and non-severe complications was low, at 0.08 and 1.5%, respectively ( 74 ) and 0.07 and 7.3%, respectively ( 31 ). Nephrogenic systemic fibrosis related to gadolinium contrast appears to be rare, with fewer than 1,000 cases reported.…”
Section: Safety and Limitations Of Stress Cmrmentioning
confidence: 99%
“…In a recent large multicenter trial of nearly 12,000 patients, CMR showed a favorable safety profile with extremely low incidence of serious immediate complications [38]. Technological advances in CMR and automated image acquisition techniques are facilitating reduced scan time and increased utilization.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%